2020
DOI: 10.3390/genes11101206
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Risk of Autism Spectrum Disorder in a Pakistani Population

Abstract: Autism spectrum disorder (ASD) is a group of complex multifactorial neurodevelopmental and neuropsychiatric disorders in children characterized by impairment of communication and social interaction. Several genes with associated single nucleotide polymorphisms (SNPs) have been identified for ASD in different genetic association studies, meta-analyses, and genome-wide association studies (GWAS). However, associations between different SNPs and ASD vary from population to population. Four SNPs in genes CNTNAP2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 81 publications
0
8
0
Order By: Relevance
“…Researchers found that despite the absence of behavioral abnormalities homozygotes for the risk allele (T) showed significant cerebral morphological variation, including reductions in grey and white matter volume in several regions (cerebellum, fusiform gyrus, and occipital and frontal cortices) that have already been implicated in ASD, suggesting that this polymorphism could disrupt frontal-occipital connections (Peñagarikano and Geschwind, 2012). In the Pakistani population, it was shown that A/T in rs7794745 of CNTNAP2 is a risk genotype for ASD (Khalid et al, 2020). According to (Nascimento et al, 2016), a research finding on the Brazilian population reported this SNP is a susceptible factor for the Brazilian population while (Werling et al, 2016) found no association with the population of Zurich.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers found that despite the absence of behavioral abnormalities homozygotes for the risk allele (T) showed significant cerebral morphological variation, including reductions in grey and white matter volume in several regions (cerebellum, fusiform gyrus, and occipital and frontal cortices) that have already been implicated in ASD, suggesting that this polymorphism could disrupt frontal-occipital connections (Peñagarikano and Geschwind, 2012). In the Pakistani population, it was shown that A/T in rs7794745 of CNTNAP2 is a risk genotype for ASD (Khalid et al, 2020). According to (Nascimento et al, 2016), a research finding on the Brazilian population reported this SNP is a susceptible factor for the Brazilian population while (Werling et al, 2016) found no association with the population of Zurich.…”
Section: Introductionmentioning
confidence: 99%
“…1 It is mainly caused by chromosomal abnormalities, gene mutations and exposure of offspring to viral or bacterial infection. 2 In recent years, ASD has shown an increase in prevalence. The American Academy of Pediatrics has reported a prevalence rate of 1 outof 91 children in the age group of 3-17 years.…”
Section: Introductionmentioning
confidence: 99%
“…This paper aims to explore the mothers' experiences, their conceptions about autism and how they interact with the child in relation to the world around them. Examining mothers' experiences raising an Autistic child in Pakistan has been challenging; as parents are often surrounded by the social stigma surrounding mental disorders (Khalid et al, 2020). This results in under reporting such cases, which makes new parents of an Autistic child feel further alienated.…”
Section: Introductionmentioning
confidence: 99%